2010
DOI: 10.1243/09544097jrrt413
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the behaviour of selected ultrasonic guided wave modes to inspect rails for long-range testing and monitoring

Abstract: Long-range ultrasonic testing (LRUT) uses guided waves in the kilohertz range to inspect many metres of an elongated component from a single point of access. This has considerable advantages for the rapid testing of long lengths for the detection of potentially harmful defects. This technique is well developed for structures that have a simple geometry, such as plates, rods, and pipes. However, this is a relatively new technology and there is still much to learn about the behaviour of guided waves and their ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…The results showed that a crack with 5 mm in depth is detectable at a distance of 4 m (from sensor to defect). 150 Commercial guided wave ultrasonic system, Teletest, was used as an arbitrary function generator to excite the PZT and to collect the responses from the rail. A combination of features, such as the first-order statistics from time domain, power spectral density (PSD) measures, and wavelet features, was extracted to perform damage classification based on the support vector machine (SVM).…”
Section: Long-range Rail Ndt Technologies Based On Guided Wavementioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that a crack with 5 mm in depth is detectable at a distance of 4 m (from sensor to defect). 150 Commercial guided wave ultrasonic system, Teletest, was used as an arbitrary function generator to excite the PZT and to collect the responses from the rail. A combination of features, such as the first-order statistics from time domain, power spectral density (PSD) measures, and wavelet features, was extracted to perform damage classification based on the support vector machine (SVM).…”
Section: Long-range Rail Ndt Technologies Based On Guided Wavementioning
confidence: 99%
“…The prototype of the Welding Institute (TWI) was developed in the MONITORAIL project, funded by the European Union, and it was in the stage of laboratory test only. [150][151][152][153] The system employed the piezoelectric elements (PZT) that were permanently bonded onto the rail surface (head, web, and foot), as shown in Figure 13. The locations where PZTs were attached to the rail cross section were chosen carefully, so that specific wave modes that uniquely occur in each section (head, web, and foot) can be generated.…”
Section: Contact Transducers Excitationmentioning
confidence: 99%
“…The selection of modes that are confined in the foot was carried out by following the development carried out in the frame of the Monitorail project. 81 Actually, a suitable excitation, which is based on piezoelectric elements around rail circumference (Figure 9(d)), has been developed in the said project 78,8284 in order to examine different portions of the rail cross-section, including the foot.…”
Section: Defect Detectionmentioning
confidence: 99%
“…Substitute the Equations (13) and (14) into the Equation (12) to obtain the Equation (15). ( 15) Similarly, the displacement and phase of transducer array 0#, 1#, 2#, 3#, and 4# can be derived as Equation 16 Transducer 0# is an excitation signal without time delay.…”
Section: Mode Enhancement Theory Based On Phase Control and Time Delamentioning
confidence: 99%
“…In addition, some scholars chose the modes to detect the damage of different parts of the rail based on the mode energy distribution. Gharaibeh et al [14] selected the mode with energy concentrated on the rail head to detect the rail head defect. And the signal was excited according to the experimental method.…”
Section: Introductionmentioning
confidence: 99%